?ON GENERALIZATION OF BANACH'S FIXED POINT THEOREM (Biological Sciences - PJSIR, 1999)
The most famous Banach's contraction principle (Banach 1992) states that a contraction mapping on a complete metric space (x, d) has a unique fixed point.